1989
DOI: 10.1093/bja/63.5.561
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Halothane on Motor Evoked Potential Recorded in the Extradural Space

Abstract: We studied the effects of supplementing nitrous oxide-oxygen anaesthesia with halothane (1 MAC end-tidal concentration) on the motor evoked potential recorded in the extradural space of eight patients before corrective surgery for idiopathic adolescent scoliosis. The motor cortex was stimulated electrically through the scalp. An additional eight patients in whom anaesthesia was supplemented with an infusion of propofol acted as a control group. Halothane had no significant effect on the amplitude or latency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…In the former, there would be a change in the descending corticospinal volley recorded using extradural electrodes; in the latter there would be no such change. Loughnan and colleagues [19] have reported that halothane and propofol do not alter the corticospinal volley in extradural recordings, but these findings did not accord with our anecdotal experience.…”
contrasting
confidence: 85%
See 1 more Smart Citation
“…In the former, there would be a change in the descending corticospinal volley recorded using extradural electrodes; in the latter there would be no such change. Loughnan and colleagues [19] have reported that halothane and propofol do not alter the corticospinal volley in extradural recordings, but these findings did not accord with our anecdotal experience.…”
contrasting
confidence: 85%
“…It is unlikely that fentanyl can cause the increase in I waves and thus the changes are attributed to isoflurane withdrawal. In addition, Loughnan and co-workers [19] observed infrequent small I waves when using halothane or propofol in addition to nitrous oxide. These observations suggest that depression of I waves may represent a fundamental difference in effect between an anaesthetic agent which primarily produces unconsciousness, such as the volatile agents or propofol, and one which has a large analgesic component to its action, such as nitrous oxide or an opioid.…”
Section: Discussionmentioning
confidence: 99%
“…The belief that the D wave produced by electrical stimulation does not change when the excitability of motor cortex changes is supported by observations on the effects of withdrawing inhalational anaesthetics (Loughnan, Anderson, Hetreed, Weston, Boyd & Hall, 1989), observations not consistent with our own unpublished experience. The present study was therefore undertaken to test the assumption that the corticospinal volley evoked by transcranial electrical stimulation is resistant to changes in motor cortex excitability.…”
Section: Introductionmentioning
confidence: 57%
“…It has been reported that muscle MEPs are suppressed by midazolam, volatile anesthetics, and even propofol in a dose-dependent manner. 4,9,10,12,14,16,20,21,25,28,29 Since muscle MEPs are known to be sensitive to volatile anesthetics, intravenous anesthetics are preferentially used during muscle MEP monitoring. 12,25 The bispectral index (BIS) is one of several methods used to monitor the depth of anesthesia.…”
mentioning
confidence: 99%